Electrogram‐guided endomyocardial biopsy yield in patients with suspected cardiac sarcoidosis and relation to outcomes. (9th August 2021) - Ezzeddine, Fatima M.; Kapa, Suraj; Rosenbaum, Andrew; Blauwet, Lori; Deshmukh, Abhishek J.; AbouEzzeddine, Omar F.; Maleszewski, Joseph J.; Asirvatham, Samuel J.; Bois, John P.; Schirger, John A.; Chareonthaitawee, Panithaya; Siontis, Konstantinos C.
Abstract: Objective: Endomyocardial biopsy (EMB) is a useful diagnostic tool though the yield may be limited in many myocardial diseases. Data on the diagnostic yield and prognostic significance of EMB guided by abnormal electrograms (EGM‐Bx) in suspected cardiac sarcoidosis (CS) are scarce. Methods: Seventy‐nine patients (mean age: 56 ± 12 years; 61% men) with suspected CS based on clinical and imaging features underwent right or left ventricular EGM‐Bx guided by electroanatomic mapping. Tissue samples were obtained from sites with abnormal EGMs and/or abnormal cardiac imaging. The diagnostic yield of EGM‐Bx was evaluated in reference to histopathologic analysis. Left ventricular assist device (LVAD) and transplantation‐free survival were compared between patients with positive and negative EGM‐Bx for CS. Results: A total of 254 samples were obtained from abnormal EGM sites, and 126 samples from normal EGM sites guided by pre‐procedure imaging findings. Abnormal histopathology was noted in 65 (26%) and 10 (8%) samples from abnormal and normal EGM sites, respectively. Histopathology confirmed CS in 16 (20%) patients, while an alternative tissue diagnosis emerged in 10 (13%) patients. Abnormal EGMs at the biopsy site had sensitivity 89% and specificity 33% for a histopathologic diagnosis of CS. LVAD and transplantation‐free survival were not significantly associated with the EGM‐Bx result (log‐rank p  = .91). Conclusion: In patients with suspected CS, abnormal EGM‐Bx has high sensitivity and low specificity for establishing a definite CS diagnosis. Consideration of substrate abnormalities apparent on preprocedural imaging as an adjunct for selection of biopsy sites may further improve EGM‐Bx yield.